Concepções de matemática expressas nos documentos oficiais da educação de jovens e adultos no período de 1930 a 2006 no Brasil - Silva, Maria Isabel Lopes (2011)
This research presents the results of a study of the mathematics concepts expressed in campaigns, regional movements and programs organized by civil society for the provision of adult education mode today entitled Youth and Adult Education. The construction of this work is based on data expressed in laws, plans, proposals, projects and use of teaching materials, categorized in the research as official documents of the sport Youth and Adult Education from 1930 to 2006. The clipping of the studied phenomenon outlined four chapters qualitative of nature, with documentary and bibliographic approach about which developed this research, being treated in the first survey contextualized campaigns, movements and national Youth and Adult Education programs. The second chapter contextualizes the first part of the teaching of mathematics in each decade of the cutout related to the perspectives of teaching and learning influenced by traditional or contemporary model understood in the context of the Youth and Adult Education. In the third chapter is an analysis and justify the theoretical framework of Chapters I and II with the cataloged documents as reference. The research points moments that the traditional conception prevails in the mechanical processes of arithmetic with decontextualized exercises, and the times when the traces of changes are highlighted by the use of the theory of set and concrete materials, with the ideals of Modern Mathematics. The contemporary design was identified by the methodological guidelines of pedagogical actions in context math, built in the relationship with the environment, enabling the dynamic practice for citizenship. Investigate the mathematical concepts expressed in the documents of Youth and Adult Education has made this study enriched by the relational perspective between discourse and practice.